• (2x+3)^2 - 7x = (2x-1)(2x+1)
    Решите уравнение.
    7 класс.

Ответы 2

  • (2x + 3)² - 7x = (2x - 1)(2x + 1)4x² + 12x + 9 - 7x = 4x² - 14x² - 4x² + 12x - 7x = -1 - 95x = -10x = -2Ответ: -2
    • Автор:

      freckles
    • 5 лет назад
    • 0
  • (2х+3)(2х+3)-7х=4х^2-14х^2+6х+6х+9-7x-4x^2+1=012x+9-7x-1=05x+10=05x=-10          /:5x=-2Ответ: х=-2
    • Автор:

      Ángel63
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years